Contornos jurídicos do status do refugiado no Brasil: desafios para a efetividade do direito à dignidade humana - Garcia, Luana Aparecida Zuppi (2016)
The study of immigrants under the refuge condition deals with the existing conditions for worldwide recognition of the need that individual to seek refuge in a country that is not their original home. This refuge is from a variety of different sources and motivations such as their ethnicity, culture, political opinion, religion or any other that endangers the fulfillment of the value of human dignity, as shown as sufficient reason for the search the refuge. The foreign country which accept those in refugee situation need to deal with the recognition of human rights of these refugees, internalizing and from the modern constitutionalist movement, recognize the existence of fundamental rights to its national and must extended to those victimized individuals and they are in refugee situation, in view of the primacy of the principle of equality. This refuge in turn need to be given by internal administrative procedure involving a wide range of government and non-government agencies for full compliance to each alleged refugee. This analysis uses the deductive research and historical methods, taking into consideration the theoretical normative UNHCR and CONARE, as well as the principles contained in international conventions and treaties on the refuge, also taking the doctrinal teachings of a range of writers on the subject discoursed. The study concludes the existing challenges in Brazil, in order to fully grasp the fundamental rights of full access to health, education, labor and employment and housing of these refugees, so as to effectively reach the value of human dignity.